Perception and kairomonal response of the coccinellid predator (Harmonia axyridis) to the fall armyworm (Spodoptera frugiperda) sex pheromone - Zhan, Yidi; Wang, Jiaojiao; Kong, Xiaona; Liu, Yong (Frontiers in Physiology, 2023)
Pheromone cues released from hosts or prey are of crucial importance to natural enemies for prey and habitat location. The use of herbivorous insect sex pheromones has long been considered as a potential pest control alternative that is nontoxic and harmless to beneficials. We hypothesized that Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae), a major predatory coccinellid beetle of the devastating migratory pest Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae), could perceive and use the sex pheromone of S. frugiperda to locate its habitat. Here we tested the electrophysiological and behavioral responses of H. axyridis to the two components Z7-12:Ac and Z9-14:Ac of S. frugiperda sex pheromone by using electroantennography (EAG) and Y-tube bioassay. The 3D modeling of H. axyridis odorant-binding proteins (HaxyOBPs) and molecular docking were also performed. The results showed that both female and male H. axyridis exhibited significantly higher electrophysiological and behavioral responses to Z9-14:Ac at the concentrations of 0.001, 0.01, and 0.1 μg/μL, while no significant electrophysiological and behavioral responses of H. axyridis were observed to Z7-12:Ac. The blend of Z7-12:Ac and Z9-14:Ac at the ratio of 1:100 had a significant attraction to both male and female H. axyridis at the concentrations of 0.01 and 0.1 μg/μL based on electrophysiological and behavioral assays, but no significant behavioral responses were observed at the ratios of 1:9. According to the 3D modeling of HaxyOBPs and molecular docking, HaxyOBP12 has a good affinity with Z9-14:Ac. Z9-14:Ac is bound to the HaxyOBP12 by hydrogen bonding and hydrophobic interactions. However, there were no credible docking results between HaxyOBPs and Z7-12:Ac. Our findings revealed that H. axyridis can perceive Z9-14:Ac and could use it as a chemical cue to locate prey habitat. We speculated that Z7-12:Ac, which showed some antagonistic effect toward the response of H. axyridis to Z9-14:Ac, could improve the adaptability of S. frugiperda in the presence of predators. This study provides new insights into the application of pheromones to manipulate natural enemy behavior for pest control.